An Atrial Septal Ridge Diagnosed by Transesophageal Echocardiography - Rowa H. Attar; Amr Telmesani; Nadeen N. Faza (Methodist DeBakey Cardiovascular Journal)
A left atrial ridge is an anomaly of irregular fusion between the septum primum and septum secundum.1 Aberrant fusion of the septa results in thickened and fibrotic tissue along the region of the fossa ovalis that will occasionally protrude into the left atrium.2 The presence of a left atrial ridge has multiple clinical implications due to its close proximity to the fossa ovalis. The location of this uncommon incongruence may make transseptal catheter-based approaches more challenging, underscoring the importance of imaging guidance to determine the ideal transseptal puncture site. Figure 1 shows cardiac images of a 64-year-old female with a history of severe mitral regurgitation, atrial fibrillation, sick sinus syndrome status post pacemaker implantation, pulmonary hypertension, systemic lupus erythematosus, and chronic kidney disease. She was seen by the valve team and underwent a transesophageal echocardiogram (TEE) to determine candidacy for transcatheter edge-to-edge repair of the mitral valve. Two-dimensional biplane imaging of the interatrial septum (IAS) shows a linear structure on the left atrial side of the fossa ovalis. Three-dimensional imaging of the IAS revealed that the structure was consistent with an atrial septal ridge.